2021
DOI: 10.1002/jmv.26896
|View full text |Cite
|
Sign up to set email alerts
|

High performance of a novel antigen detection test on nasopharyngeal specimens for diagnosing SARS‐CoV‐2 infection

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has become a major public health issue worldwide. Developing and evaluating rapid and easy-to-perform diagnostic tests is a high priority. The current study was designed to assess the diagnostic performance of an antigen-based rapid detection test (COVID-VIRO ® ) in a real-life setting. Two nasopharyngeal specimens of symptomatic or asymptomatic adult patients hospitalized in the Infectious Diseases Department or voluntarily accessing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 29 publications
3
49
0
Order By: Relevance
“…Studies that evaluated different types of samples revealed that nasal examination swabs and saliva specimens for RDTs are associated with lower sensitivity (30). Our results showed the most collected samples were nasopharyngeal swabs; in this line, it was shown examine nasopharyngeal swab, the sensitivity of RDTs results increases (10,41). After evaluating various specimens, Yamayoshi et al found that soaking specimen directly to the lysing buffer can improve RDTs sensitivity (41).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Studies that evaluated different types of samples revealed that nasal examination swabs and saliva specimens for RDTs are associated with lower sensitivity (30). Our results showed the most collected samples were nasopharyngeal swabs; in this line, it was shown examine nasopharyngeal swab, the sensitivity of RDTs results increases (10,41). After evaluating various specimens, Yamayoshi et al found that soaking specimen directly to the lysing buffer can improve RDTs sensitivity (41).…”
Section: Discussionsupporting
confidence: 58%
“…The possible interference of time of testing cannot be ruled out. Some researchers revealed that testing less than 5 days from the onset of symptoms increases sensitivity (9,10,23,31). It is inconsistent with previous reports that a load of infectious virus decreases after 7-10 days (10,45).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The sensitivity of antigen detection tests are generally lower than that of nucleic acid tests, even though their specificity are comparable. Currently, a new COVID-19 antigen detection test with higher sensitivity (greater than 95%) and 100% specificity is available [3]. Antigen detection tests with high sensitivity and specificity are expected to play an increasingly important role in the early diagnosis of SARS-CoV-2 infection and will be more useful in hospitals, communities, and airports around the world.…”
Section: Advantages Of Antigen Detection Testsmentioning
confidence: 99%